2002
DOI: 10.1146/annurev.publhealth.23.100901.140551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking Restrictions in the Workplace

Abstract: Key Words attitudes, behavior, public policy, tobacco smoke pollution s Abstract The health hazards caused by exposure to environmental tobacco smoke (ETS) are well established. Workplace exposure to ETS is strongly influenced by the types of workplace and smoking policy-total bans on smoking have become common in many countries. Blue-collar and service workers are more likely than other types of workers to be exposed to ETS in the workplace. Smokers who are employed in workplaces with smoking bans are likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 41 publications
3
84
0
2
Order By: Relevance
“…In addition to worksite studies, bans on smoking in restaurants and bars also result in lowered exposure rates for community residents (2). Studies have also shown that complete smoking bans are more effective at reducing ETS exposure than smoking restrictions (17).…”
Section: Physical Environment/accessmentioning
confidence: 99%
“…In addition to worksite studies, bans on smoking in restaurants and bars also result in lowered exposure rates for community residents (2). Studies have also shown that complete smoking bans are more effective at reducing ETS exposure than smoking restrictions (17).…”
Section: Physical Environment/accessmentioning
confidence: 99%
“…While the impact of maternal smoking on the fetus has received considerable attention in the medical literature (Kramer 1987), with its deleterious effects ranging from low birth weight and other birth defects, to childhood and adult asthma and lower cognitive functioning (Horta, Victora, Menezes, Halpern, and Barros 1997;Sayer and Kleinenman 2002;Weitzman, Gortmaker, Walker, and Sobol 1990;Dolan-Mullen, Ramirez, and Groff 1994), the impacts of exposure to second hand smoke is less well studied. On the policy side, while many papers have examined the immediate impacts of taxes or smoking bans on smoking behavior (Brownson, Hopkins, and Wakefield 2002;Eagan, Hetland, and Aarø 2006;Farkas, Gilpin, Distefan, and Pierce 1999;Bitler, Carpenter, and Zavodny 2011;Anger, Kvasnicka, and Siedler 2011), few papers in the economics literature have examined the consequences of such policies on birth outcomes. Evans and Ringel (2001), Lien and Evans (2005) and Simon (2012) are some of the papers that do examine the impact of such policies on smoking during pregnancy and birth outcomes, however, their policy focus is on changes in cigarette taxes rather than smoking bans.…”
Section: Introductionmentioning
confidence: 99%
“…Enforcement of tobacco free premises in any environment has been shown to reduce the prevalence and consumption of tobacco use 15,16 . This directly reduces environmental tobacco smoke (ETS) and, its health effects.…”
Section: Discussionmentioning
confidence: 99%